Poisoning by Plants - Wendt, Sebastian; Lübbert, Christoph; Begemann, Kathrin; Prasa, Dagmar; Franke, Heike (Deutsches Ärzteblatt international, 2022)
Questions on poisoning by plants are a common reason for inquiries to poison information centers (PIC). Over the years 2011-2020, plant poisoning was the subject of 15% of all inquiries to the joint poison information center in Erfurt, Germany (Gemeinsames Giftinformationszentrum Erfurt, GGIZ) that concerned poisoning in children (2.3% in adults). In this patient collective, plant poisoning occupied third place after medical drugs (32%) and chemical substances (24%), and was a more common subject of inquiry than mushroom poisoning (1.5%). This review is based on pertinent publications retrieved by a selective literature search in PubMed/TOXLINE on plant poisoning and on 12 epidemiologically and toxicologically relevant domestic species of poisonous plants in risk categories 2 and 3 (up to 2021). Medical personnel should have basic toxicological knowledge of the following highly poisonous plants: wolfsbane (aconitum), belladonna, angel's trumpet, cowbane (cicuta virosa), autumn crocus, hemlock, jimson weed, henbane, castor bean (ricinus), false hellebore, foxglove (digitalis), and European yew. The intoxication is evaluated on the basis of a structured history (the "w" questions) and the clinical manifestations (e.g., toxidromes). Special analysis is generally not readily available and often expensive and time-consuming. In case of poisoning, a poison information center should be contacted for plant identification, risk assessment, and treatment recommendations. Specimens of plant components and vomit should be obtained, if possible, for further testing. Measures for the elimination of the poisonous substance may be indicated after a risk-benefit analysis. Specific antidotes are available for only a few types of plant poisoning, e.g., physostigmine for tropane alkaloid poisoning or digitalis antibodies for foxglove poisoning. The treatment is usually symptomatic and only rarely evidence-based. Individualized medical surveillance is recommended after the ingestion of large or unknown quantities of poisonous plant components. The clinician should be able to recognize dangerous domestic species of poisonous plants, take appropriate initial measures, and avoid overdiagnosis and overtreatment. To improve patient care, systematic epidemiological and clinical studies are needed.